Mobile Application (Handy Mall) for Shopping Mall Malaysia - Modern Mall Application - Bin Hishammuddin, Muhamad Faiz (Journal of Computing Technologies and Creative Content, 2019)
Smartphones part of everyday life for most people (Mukherjea, 2017). A mobile application referred to as an app. Apps are small application and singular software units with limited functions. Existing mall mobile application used as guide for users in the mall to get the accurate information. Most mall mobile application focus on listing outlet brand, promotion and location of outlets. Mall application also help the user to keep update with latest event and promotion that took place at the mall. Handy mall application focus on outlets items directory. Handy mall application helps the user to view new arrival and available products in the outlets. This application able to improve consumer experience before going to the mall such as save time and not need to come to the mall for check whether the product is available in the outlet. Basically, this feature been used on every e-commerce website but not for mall mobile application.